Financial Performance And Its Implications On The Profitability Of Banks Listed On The Indonesia Stock Exchange (IDX) - Fauzan Abi Rafdi; Mustanwir Zuhri (Journal of Business, Finance, and Banking, 2026)
Abstract – This research objective is to analyze and examine the influence of capital adequacy ratio (CAR), non-performing loan (NPL), operational expenses to operational income ratio (BOPO), and loan to deposit ratio (LDR) on return on assets (ROA) in banking sector companies listed in the Indonesia Stock Exchange (Jakarta Stock Exchange). The data used are the financial ratios of banks from 2018 to 2022. The sample size for this study consists of 10 companies selected using purposive sampling method. The data analysis technique used is panel data regression analysis, processed using Eviews 9.0 application following the random effect model. The results of this research indicate that CAR and LDR have no effect on return on assets (ROA), while NPL and BOPO have negative effect on return on assets (ROA). Keywords: Return on assets, capital adequacy ratio, nonperforming loan, operational expenses and operational income, loan to deposit ratio